2016
DOI: 10.1002/ar.23353
|View full text |Cite
|
Sign up to set email alerts
|

Ellis Van Creveld2 is Required for Postnatal Craniofacial Bone Development

Abstract: Ellis-van Creveld (EvC) syndrome is a genetic disorder with mutations in either EVC or EVC2 gene. Previous case studies reported that EvC patients underwent orthodontic treatment, suggesting the presence of craniofacial bone phenotypes. To investigate whether a mutation in EVC2 gene causes a craniofacial bone phenotype, Evc2 knockout (KO) mice were generated and cephalometric analysis was performed. The heads of wild type (WT), heterozygous (Het) and homozygous Evc2 KO mice (1-, 3- and 6-week-old) were prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 26 publications
3
15
0
Order By: Relevance
“…In the current studies, we identified that the skull length, nasal bone length, frontal bone length, incisor length, and total cranial base length are all significantly smaller in Evc2 m mutants than in controls at postnatal day 8. These observations are consistent with previous reports using different methods to study abnormal craniofacial development (Badri et al, ) and abnormal tooth development (Zhang et al, ). Our previous studies demonstrated that Evc2 is expressed in nearly all tissues in the skull (Badri et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current studies, we identified that the skull length, nasal bone length, frontal bone length, incisor length, and total cranial base length are all significantly smaller in Evc2 m mutants than in controls at postnatal day 8. These observations are consistent with previous reports using different methods to study abnormal craniofacial development (Badri et al, ) and abnormal tooth development (Zhang et al, ). Our previous studies demonstrated that Evc2 is expressed in nearly all tissues in the skull (Badri et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…At postnatal day 8, Evc2 m exhibited smaller skull size compared to the control group. The gross morphology demonstrated in the Evc2 mutant mice is similar both to phenotypes of Evc mutant mice (Ruiz‐Perez et al, ; Pacheco et al, ; Badri et al, ) and to symptoms observed in EvC patients (Ellis and van Creveld, ; McKusick et al, ). These facts suggest that the molecular pathological mechanism leading to craniofacial abnormalities in Evc2 mutant mice is the same as those in Evc mutant mice and in EvC patients.…”
Section: Discussionsupporting
confidence: 68%
“…Radiograph-based cephalometry used in murine skulls is very similar to that used in human, which has practical and successful clinical applications. Although it was reported that certain landmarks are difficult to identify on two-dimensional radiograph of mouse skull (Bloom et al, 2006 ), radiograph-based cephalometry has been used successfully to identify morphometric changes in transgenic mice (Chung et al, 1997 ; McAlarney et al, 2001 ; Yagasaki et al, 2003 ; Simon et al, 2014 ; Badri et al, 2016 ). Thus, radiograph-based cephalometric analysis is an alternative to μCT-based craniofacial morphological measurement when the landmarks can be clearly identified.…”
Section: Discussionmentioning
confidence: 99%
“…Generating our own Evc2 mutant mice enabled us to characterize the pathological mechanisms leading to abnormal appendicular bone and hypomorphic enamel development ( Zhang et al, 2015 , 2016a , b ). Our subsequent studies further demonstrated the expression of Evc2 in the mid-facial regions ( Badri et al, 2016a ) and mid-facial defects in Evc2 global mutant mice ( Badri et al, 2016b ). We most recently employed a conditional, Cre -mediated approach toward deleting Evc2 in a neural crest-specific manner.…”
Section: Introductionmentioning
confidence: 74%
“…Our previous studies indicated that global Evc2 mutation led to retarded growth and significantly affected both body and head size ( Zhang et al, 2015 ; Badri et al, 2016b ). To better characterize the function of Evc2 in craniofacial development, we generated mutant mice with Evc2 deleted in the neural crest-derived cells.…”
Section: Resultsmentioning
confidence: 99%